Study of Resonator Properties of Stable and Unstable Lasers - Zeina Abdul Rahman; Zeyad Ahmed (College of Education for Pure Sciences, 2019)
In this work, the stability of optical resonator for two types of lasers are studied which are, He-Ne laser and CO2 laser. The first type, is a low power laser and 0.6328 µm of wave length and  the second type (CO2 laser) is a high power laser and 10.6 µm of wave length . Theoretical part deals with illustrating the physical meaning of stability factors which are g-factor, Fresnel No. , Q-factor and diffraction losses , also the mathematical equations of these factors and the geometrical specifications related  with optical resonator. According to the figures which show the relationships between the stability factors, He-Ne laser is more stable than CO2 laser ; it has been verified and this is due to the high difference of photon ,s energy and also to the difference in output powers for the two laser.